A medical antibacterial coating and preparation method thereof

Through a two-step anodization method and composite surface modification technology, a composite antibacterial coating is formed, which solves the problems of insignificant antibacterial effect and poor antibacterial stability in the existing technology, and achieves efficient, stable antibacterial performance and good biocompatibility. .

CN118880325BActive Publication Date: 2025-01-24SUZHOU HOUFENGYUAN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411354050.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing medical antibacterial coatings for titanium and titanium alloy surfaces have problems such as insignificant antibacterial effect, poor antibacterial stability, poor biocompatibility, weak binding strength and high cost.

Method used

A two-step anodizing method is used for surface micro-nano modification, combined with electrophoretic deposition of iodine, ion implantation of zinc, and surface modification of povidone iodine/food grade water-soluble chitosan to form a composite antibacterial coating.

Benefits of technology

A medical antibacterial coating with significant antibacterial effects, sufficient antibacterial stability, good biocompatibility, strong combination and high cost performance, suitable for continuous and large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a medical antibacterial coating and a preparation method thereof, which relates to the technical field of biomedical materials, and comprises the following steps: step S1, pretreatment; step S2, two-step anodization; step S3, electrophoretic deposition of iodine; step S4, zinc loading; step S5, surface modification. The medical antibacterial coating has significant antibacterial effect, sufficient antibacterial stability, good biocompatibility, strong bonding force, and high cost performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a medical antibacterial coating and a preparation method thereof. Background Art

[0002] Titanium and titanium alloys have gradually become the preferred materials for dental implants, bone trauma products, artificial joints and other human hard tissue substitutes and repairs due to their excellent biocompatibility, corrosion resistance and comprehensive mechanical properties. However, when used as implants, titanium and titanium alloys have defects such as biological inertness, poor bone regeneration ability, and poor integration with surrounding tissues. More seriously, due to the lack of antibacterial properties on the surface of titanium and titanium alloys, bacteria easily adhere and form biofilms, and have strong drug resistance, thus causing secondary infection and leading to implant failure. Therefore, through appropriate surface treatment and modification, various surface properties such as biocompatibility, bioactivity, wear resistance and antibacterial properties can be effectively improved on the basis of retaining the original excellent properties of titanium and titanium alloys, thereby improving the efficacy and service life of the implant and alleviating the pain of patients.

[0003] By loading silver and other active components on the surface of titanium and titanium alloys, their antibacterial properties and biological activity can be improved. However, the silver active components loaded on the surface of titanium and titanium alloys have technical defects such as high price, poor mildew resistance and poor color stability. As substitutes for silver, copper, zinc, rare earth elements and their micro-nano oxides, etc., also have technical bottlenecks such as poor antibacterial properties. In addition, other medical antibacterial coatings on the surface of titanium and titanium alloys on the market also have more or less defects such as high cost, weak bonding strength and poor durability.

[0004] For example, the Chinese invention patent with the authorization announcement number CN102758202B discloses a method for preparing an antibacterial coating on the surface of medical titanium and titanium alloys, which is as follows: 1. After the surface of the medical titanium or titanium alloy sample to be treated is treated, it is immersed in an ethylene glycol aqueous solution containing soluble fluoride for anodizing treatment; 2. The medical titanium or titanium alloy sample after anodizing is immersed in an AgNO3 solution, taken out and treated with ultraviolet radiation to obtain a silver-loaded medical titanium or titanium alloy sample; 3. The silver-loaded medical titanium or titanium alloy sample is subjected to micro-arc oxidation treatment, ultrasonic cleaning, and vacuum drying to obtain an antibacterial coating. This invention combines the preparation of nano-precoating, silver-loading treatment and micro-arc oxidation technology to achieve a large amount of silver fixation and long-term slow release on the surface of medical titanium and titanium alloys, which can significantly improve the antibacterial properties of titanium and titanium alloys, and enable the antibacterial effect to be maintained for a long time, greatly reducing or avoiding bacterial infections caused by titanium and titanium alloy devices implanted in the human body. However, since it uses silver loading, its preparation cost is relatively high, and the leakage of a large amount of silver ions has certain negative effects on the human body.

[0005] In view of this, the art still needs a medical antibacterial coating with significant antibacterial effect, sufficient antibacterial stability, good biocompatibility, strong binding force, and high cost performance, and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a medical antibacterial coating having significant antibacterial effect, sufficient antibacterial stability, good biocompatibility, strong binding force and high cost performance, and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a medical antibacterial coating, comprising the following steps:

[0008] Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample;

[0009] Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 0.5-1h, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; use a multi-energy field assisted treatment for 10-15min in the first step of anodization; use a multi-energy field assisted treatment for 15-20min in the second step of anodization;

[0010] Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition solution, the sample with micro-nano surface modification as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample;

[0011] Step S4, loading zinc: using ion implantation method, with zinc as the target material, injecting zinc into the iodine-loaded sample to obtain a sample with iodine / zinc loaded on the surface;

[0012] Step S5, surface modification: immerse the iodine / zinc loaded sample prepared in step S4 in a povidone iodine / food grade water-soluble chitosan dipping solution for 8-25 seconds, take it out and dry it to constant weight to obtain a medical antibacterial coating.

[0013] Preferably, the ultrasonic frequency of the ultrasonic cleaning is 60-100kHz and the power is 300-400W.

[0014] Preferably, the fluorine-containing electrolyte in step S2 includes the following components in percentage by weight: 0.5-2.5wt% ammonium fluoride, 20-30wt% glycerol, 1-3wt% tris(hydroxymethyl)aminomethanesulfonic acid, 0.3-1wt% saccharin sodium, 0.1-0.6wt% hexamethylenetetramine, 1-3wt% citric acid, 0.1-0.4wt% calcium dihydrogen phosphate, and the balance is deionized water.

[0015] Preferably, the parameters of the first step of anodization in step S2 are: voltage of 40 to 100 V, distance between the anode and the cathode of 8 to 15 cm, temperature of 20 to 30° C., and time of 1 to 3 h.

[0016] Preferably, the volume percentage concentration of the hydrochloric acid solution in step S2 is 4-20 vol%.

[0017] Preferably, the parameters of the second step of anodization in step S2 are: voltage of 18 to 52 V, distance between the anode and cathode of 5 to 10 cm, temperature of 20 to 30° C., and time of 3 to 6 h.

[0018] Preferably, the calcination temperature in step S2 is 440-610° C., and the calcination time is 1-5 hours.

[0019] Preferably, the multi-energy field includes ultrasound, microwave and steady magnetic field; the ultrasound frequency is 40-80kHz, and the power is 90-310W; the microwave frequency is 2.0-2.7GHz, and the power is 550-1250W; the magnetic field strength of the steady magnetic field is 6000-16000Gs.

[0020] Preferably, the iodine salt aqueous solution in step S3 is a potassium iodide aqueous solution or a sodium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.06-0.12 mol / L.

[0021] Preferably, the parameters of the electrophoretic deposition of iodine in step S3 are: the distance between the working electrode and the counter electrode is 8 to 22 cm, the deposition time is 10 to 35 min, the constant voltage is 25 to 75 V, the temperature is 20 to 30° C., and it is carried out under light-proof conditions.

[0022] Preferably, the specific parameters of the ion implantation method in step S4 are: ion flux 140-160 keV, trigger frequency 4-7 Hz, arc voltage 70-120 V, acceleration voltage 25-50 kV, arc current 0.3-0.8 A, suppression voltage 1.5-3.5 kV, vacuum degree 1×10 -4 ~5×10 -4 Pa.

[0023] Preferably, in the povidone iodine / food-grade water-soluble chitosan dipping solution in step S5, the mass percentage concentration of food-grade water-soluble chitosan is 1-6wt%, and the mass percentage concentration of povidone iodine is 0.3-1wt%.

[0024] Preferably, the food-grade water-soluble chitosan has a viscosity-average molecular weight of 100,000-120,000 and a deacetylation degree of 90%.

[0025] Preferably, the drying temperature in step S5 is 90-95°C.

[0026] Another object of the present invention is to provide a medical antibacterial coating prepared by the above-mentioned method for preparing the medical antibacterial coating.

[0027] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0028] (1) The preparation method of the medical antibacterial coating disclosed in the present invention has simple process, convenient operation and control, low dependence on equipment, low energy consumption, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.

[0029] (2) The medical antibacterial coating disclosed in the present invention adopts a two-step anodizing method to perform surface micro-nano modification. By rationally selecting the specific parameters of the two-step anodizing, the thickness and morphology of the micro-nano structure can be controlled, the binding force can be improved, the loading amount of the antibacterial active ingredients can be effectively controlled, the diffusion and differentiation of surface osteoblasts can be promoted, and the antibacterial rate and biocompatibility can be improved; the fluorine-containing electrolyte comprises the following components in percentage by weight: 0.5-2.5wt% ammonium fluoride, 20-30wt% glycerol, 1-3wt% tris(hydroxymethyl)aminomethanesulfonic acid %, saccharin sodium 0.3-1wt%, hexamethylenetetramine 0.1-0.6wt%, citric acid 1-3wt%, calcium dihydrogen phosphate 0.1-0.4wt%, and the balance is deionized water; through the reasonable selection of the fluorine-containing electrolyte formula and the cooperation of the components, the anodizing effect and efficiency can be improved, and the bonding force between the surface micro-nano structure and titanium or titanium alloy can be improved; through multi-energy field assisted treatment, the anodizing effect and efficiency can be further improved, and a micro-nano structure with a specific morphological structure can be formed, thereby improving the bonding force, antibacterial durability and biocompatibility.

[0030] (3) The medical antibacterial coating disclosed in the present invention simultaneously adopts electrophoretic deposition to load iodine, ion implantation to load zinc, and surface modification of povidone iodine / food-grade water-soluble chitosan to form a composite antibacterial coating; a good match between antibacterial and biocompatibility is achieved, and the purpose of slowly releasing iodine in the body is achieved; the antibacterial effect and antibacterial durability are further improved through the synergistic effect of iodine, chitosan, and zinc.

[0031] (4) The medical antibacterial coating disclosed in the present invention has strong bonding force with the substrate, controllable loading amount of antibacterial active ingredients, good antibacterial effect, good antibacterial durability and good biocompatibility through the electrophoretic deposition of iodine, ion implantation of zinc and reasonable selection of process parameters for the surface modification step. The preparation effect is high, the labor intensity is low and the impact on the environment is small. The prepared coating is safe and environmentally friendly. DETAILED DESCRIPTION

[0032] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0033] Embodiment 1, a method for preparing a medical antibacterial coating, comprising the following steps:

[0034] Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample;

[0035] Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 0.5h, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; use a multi-energy field assisted treatment for 10min in the first step of anodization; use a multi-energy field assisted treatment for 15min in the second step of anodization;

[0036] Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition solution, the surface micro-nano modified sample as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample; according to the weight change and elemental analysis, the iodine loading rate is 0.55wt%;

[0037] Step S4, loading zinc: using ion implantation method, zinc is used as a target material, and zinc is implanted into the iodine-loaded sample to obtain a sample with iodine / zinc loaded on the surface; according to the weight change and elemental analysis, the loading rate of zinc is 0.28wt%;

[0038] Step S5, surface modification: immerse the iodine / zinc loaded sample prepared in step S4 in a povidone iodine / food-grade water-soluble chitosan dipping solution for 8 seconds, take it out and dry it to constant weight to obtain a medical antibacterial coating; according to the weight change and elemental analysis, the modification rate of povidone iodine is 0.11wt%, and the modification rate of food-grade water-soluble chitosan is 0.19wt%.

[0039] The ultrasonic cleaning has an ultrasonic frequency of 60 kHz and a power of 300 W.

[0040] The fluorine-containing electrolyte in step S2 includes the following components in percentage by weight: 0.5wt% ammonium fluoride, 20wt% propylene glycol, 1wt% tris(hydroxymethyl)aminomethanesulfonic acid, 0.3wt% sodium saccharin, 0.1wt% hexamethylenetetramine, 1wt% citric acid, 0.1wt% calcium dihydrogen phosphate, and the balance is deionized water.

[0041] The parameters of the first step of anodization in step S2 are: voltage of 40V, distance between anode and cathode of 8cm, temperature of 20°C, and time of 1h; the volume percentage concentration of the hydrochloric acid solution in step S2 is 4vol%; the parameters of the second step of anodization in step S2 are: voltage of 18V, distance between anode and cathode of 5cm, temperature of 20°C, and time of 3h; the calcination temperature in step S2 is 440°C, and the calcination time is 1h.

[0042] The multi-energy field includes ultrasound, microwave and steady magnetic field; the ultrasound frequency is 40kHz and the power is 90W; the microwave frequency is 2.0GHz and the power is 550W; the magnetic field strength of the steady magnetic field is 6000Gs.

[0043] The iodine salt aqueous solution in step S3 is a potassium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.06 mol / L.

[0044] The parameters of the electrophoretic deposition of iodine in step S3 are: the distance between the working electrode and the counter electrode is 8 cm, the deposition time is 10 min, the constant voltage is 25 V, the temperature is 20 ° C, and it is carried out under light-proof conditions; the specific parameters of the ion implantation method in step S4 are: ion flux 140 keV, trigger frequency 4 Hz, arc voltage 70 V, acceleration voltage 25 kV, arc current 0.3 A, suppression voltage 1.5 kV, vacuum degree 1×10 -4 .

[0045] In the povidone iodine / food-grade water-soluble chitosan dipping solution described in step S5, the mass percentage concentration of food-grade water-soluble chitosan is 1wt%, and the mass percentage concentration of povidone iodine is 0.3wt%; the viscosity-average molecular weight of the food-grade water-soluble chitosan is 100,000, and the degree of deacetylation is 90%; the drying temperature described in step S5 is 90°C.

[0046] A medical antibacterial coating prepared by the preparation method of the medical antibacterial coating.

[0047] Embodiment 2, a method for preparing a medical antibacterial coating, comprising the following steps:

[0048] Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample;

[0049] Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 0.6h, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; use a multi-energy field assisted treatment for 12min in the first step of anodization; use a multi-energy field assisted treatment for 16min in the second step of anodization;

[0050] Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition solution, the sample with micro-nano surface modification as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample;

[0051] Step S4, loading zinc: using ion implantation method, with zinc as the target material, injecting zinc into the iodine-loaded sample to obtain a sample with iodine / zinc loaded on the surface;

[0052] Step S5, surface modification: immerse the iodine / zinc loaded sample prepared in step S4 in a povidone iodine / food grade water-soluble chitosan dipping solution for 13 seconds, take it out and dry it to a constant weight to obtain a medical antibacterial coating.

[0053] The ultrasonic frequency of the ultrasonic cleaning is 70kHz and the power is 320W; the fluorine-containing electrolyte in step S2 includes the following components in weight percentage: 1wt% ammonium fluoride, 23wt% glycerol, 1.5wt% tris(hydroxymethyl)aminomethanesulfonic acid, 0.5wt% saccharin sodium, 0.2wt% hexamethylenetetramine, 1.5wt% citric acid, 0.2wt% calcium dihydrogen phosphate, and the balance is deionized water.

[0054] The parameters of the first step of anodization in step S2 are: voltage of 50V, distance between anode and cathode of 11cm, temperature of 23°C, and time of 1.5h; the volume percentage concentration of the hydrochloric acid solution in step S2 is 9vol%; the parameters of the second step of anodization in step S2 are: voltage of 32V, distance between anode and cathode of 7cm, temperature of 23°C, and time of 4h; the calcination temperature in step S2 is 500°C, and the calcination time is 2h; the multi-energy field includes ultrasound, microwave and steady magnetic field; the ultrasound frequency is 50kHz, and the power is 140W; the microwave frequency is 2.2GHz, and the power is 750W; the magnetic field strength of the steady magnetic field is 8000Gs.

[0055] The iodine salt aqueous solution in step S3 is a sodium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.08 mol / L; the parameters of the electrophoretic deposition of iodine in step S3 are: the distance between the working electrode and the counter electrode is 14 cm, the deposition time is 16 min, the constant voltage is 35 V, the temperature is 23° C., and it is carried out under light-proof conditions.

[0056] The specific parameters of the ion implantation method in step S4 are: ion flux 145 keV, trigger frequency 5 Hz, arc voltage 80 V, acceleration voltage 35 kV, arc current 0.4 A, suppression voltage 2 kV, vacuum degree 2×10 -4 Pa; in the povidone iodine / food grade water-soluble chitosan dipping solution described in step S5, the mass percentage concentration of food-grade water-soluble chitosan is 2wt%, and the mass percentage concentration of the povidone iodine is 0.5wt%; the viscosity-average molecular weight of the food-grade water-soluble chitosan is 105,000, and the degree of deacetylation is 90%; the drying temperature described in step S5 is 92°C.

[0057] A medical antibacterial coating prepared by the preparation method of the medical antibacterial coating.

[0058] Embodiment 3, a method for preparing a medical antibacterial coating, comprising the following steps:

[0059] Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample;

[0060] Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 0.7h, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; in the first step of anodization, use a multi-energy field assisted treatment for 13min; in the second step of anodization, use a multi-energy field assisted treatment for 18min;

[0061] Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition solution, the sample with micro-nano surface modification as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample;

[0062] Step S4, loading zinc: using ion implantation method, with zinc as the target material, injecting zinc into the iodine-loaded sample to obtain a sample with iodine / zinc loaded on the surface;

[0063] Step S5, surface modification: immerse the iodine / zinc loaded sample prepared in step S4 in a povidone iodine / food grade water-soluble chitosan dipping solution for 18 seconds, take it out and dry it to a constant weight to obtain a medical antibacterial coating.

[0064] The ultrasonic frequency of the ultrasonic cleaning is 80kHz and the power is 350W; the fluorine-containing electrolyte in step S2 includes the following components in weight percentage: 1.8wt% ammonium fluoride, 25wt% glycerol, 2wt% tris(hydroxymethyl)aminomethanesulfonic acid, 0.6wt% saccharin sodium, 0.4wt% hexamethylenetetramine, 2wt% citric acid, 0.25wt% calcium dihydrogen phosphate, and the balance is deionized water.

[0065] The parameters of the first step of anodization in step S2 are: voltage of 70V, distance between anode and cathode of 12cm, temperature of 25°C, and time of 2h; the volume percentage concentration of the hydrochloric acid solution in step S2 is 13vol%; the parameters of the second step of anodization in step S2 are: voltage of 42V, distance between anode and cathode of 8cm, temperature of 25°C, and time of 4.5h; the calcination temperature in step S2 is 520°C, and the calcination time is 3.5h; the multi-energy field includes ultrasound, microwave and steady magnetic field; the ultrasound frequency is 60kHz, and the power is 240W; the microwave frequency is 2.4GHz, and the power is 950W; the magnetic field strength of the steady magnetic field is 12000Gs.

[0066] The iodine salt aqueous solution in step S3 is a potassium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.09 mol / L; the parameters of the electrophoretic deposition of iodine in step S3 are: the distance between the working electrode and the counter electrode is 18 cm, the deposition time is 27 min, the constant voltage is 55 V, the temperature is 25 ° C, and it is carried out under light-proof conditions; the specific parameters of the ion implantation method in step S4 are: ion flux 150 keV, trigger frequency 5.5 Hz, arc voltage 100 V, acceleration voltage 40 kV, arc current 0.6 A, suppression voltage 2.5 kV, vacuum degree 3×10 -4 Pa; in the povidone iodine / food grade water-soluble chitosan dipping solution described in step S5, the mass percentage concentration of food-grade water-soluble chitosan is 4wt%, and the mass percentage concentration of the povidone iodine is 0.7wt%; the viscosity-average molecular weight of the food-grade water-soluble chitosan is 110,000, and the degree of deacetylation is 90%; the drying temperature described in step S5 is 93°C.

[0067] A medical antibacterial coating prepared by the preparation method of the medical antibacterial coating.

[0068] Embodiment 4, a method for preparing a medical antibacterial coating, comprising the following steps:

[0069] Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample;

[0070] Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 0.9h, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; use a multi-energy field assisted treatment for 14min in the first step of anodization; use a multi-energy field assisted treatment for 19min in the second step of anodization;

[0071] Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition solution, the sample with micro-nano surface modification as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample;

[0072] Step S4, loading zinc: using ion implantation method, with zinc as the target material, injecting zinc into the iodine-loaded sample to obtain a sample with iodine / zinc loaded on the surface;

[0073] Step S5, surface modification: immerse the iodine / zinc loaded sample prepared in step S4 in a povidone iodine / food grade water-soluble chitosan dipping solution for 23 seconds, take it out and dry it to a constant weight to obtain a medical antibacterial coating.

[0074] The ultrasonic cleaning has an ultrasonic frequency of 95 kHz and a power of 380 W.

[0075] The fluorine-containing electrolyte in step S2 includes the following components in percentage by weight: 2.3wt% ammonium fluoride, 28wt% glycerol, 2.5wt% tris(hydroxymethyl)aminomethanesulfonic acid, 0.9wt% saccharin sodium, 0.5wt% hexamethylenetetramine, 2.5wt% citric acid, 0.35wt% calcium dihydrogen phosphate, and the balance is deionized water; the parameters of the first step of anodization in step S2 are: voltage of 90V, distance between the anode and the cathode of 13cm, temperature of 28°C, and time of 2.5h; in step S2 The volume percentage concentration of the hydrochloric acid solution is 18 vol%; the parameters of the second step anodization in step S2 are: voltage of 48 V, distance between the anode and the cathode of 9 cm, temperature of 28° C., and time of 5.5 h; the calcination temperature in step S2 is 580° C., and the calcination time is 4 h; the multi-energy field includes ultrasound, microwave and steady magnetic field; the ultrasound frequency is 75 kHz, and the power is 300 W; the microwave frequency is 2.6 GHz, and the power is 1150 W; the magnetic field strength of the steady magnetic field is 15000 Gs.

[0076] The iodine salt aqueous solution in step S3 is a potassium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.11 mol / L; the parameters of the electrophoretic deposition of iodine in step S3 are: the distance between the working electrode and the counter electrode is 20 cm, the deposition time is 32 min, the constant voltage is 70 V, the temperature is 28 ° C, and it is carried out under light-proof conditions; the specific parameters of the ion implantation method in step S4 are: ion flux 155 keV, trigger frequency 6.5 Hz, arc voltage 110 V, acceleration voltage 46 kV, arc current 0.7 A, suppression voltage 3 kV, vacuum degree 4×10 -4 Pa.

[0077] In the povidone iodine / food-grade water-soluble chitosan dipping solution described in step S5, the mass percentage concentration of food-grade water-soluble chitosan is 5wt%, and the mass percentage concentration of povidone iodine is 0.9wt%; the viscosity-average molecular weight of the food-grade water-soluble chitosan is 115,000, and the degree of deacetylation is 90%; the drying temperature described in step S5 is 94°C.

[0078] A medical antibacterial coating prepared by the preparation method of the medical antibacterial coating.

[0079] Embodiment 5, a method for preparing a medical antibacterial coating, comprising the following steps:

[0080] Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample;

[0081] Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 1 hour, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; use a multi-energy field assisted treatment for 15 minutes in the first step of anodization; use a multi-energy field assisted treatment for 20 minutes in the second step of anodization;

[0082] Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition solution, the sample with micro-nano surface modification as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample;

[0083] Step S4, loading zinc: using ion implantation method, with zinc as the target material, injecting zinc into the iodine-loaded sample to obtain a sample with iodine / zinc loaded on the surface;

[0084] Step S5, surface modification: immerse the iodine / zinc loaded sample prepared in step S4 in a povidone iodine / food grade water-soluble chitosan dipping solution for 25 seconds, take it out and dry it to a constant weight to obtain a medical antibacterial coating.

[0085] The ultrasonic frequency of the ultrasonic cleaning is 100kHz and the power is 400W; the fluorine-containing electrolyte in step S2 includes the following components in weight percentage: 2.5wt% ammonium fluoride, 30wt% propylene glycol, 3wt% tris(hydroxymethyl)aminomethanesulfonic acid, 1wt% sodium saccharin, 0.6wt% hexamethylenetetramine, 3wt% citric acid, 0.4wt% calcium dihydrogen phosphate, and the balance is deionized water.

[0086] The parameters of the first step of anodization in step S2 are: voltage of 100V, distance between anode and cathode of 15cm, temperature of 30°C, and time of 3h; the volume percentage concentration of the hydrochloric acid solution in step S2 is 20vol%; the parameters of the second step of anodization in step S2 are: voltage of 52V, distance between anode and cathode of 10cm, temperature of 30°C, and time of 6h; the calcination temperature in step S2 is 610°C, and the calcination time is 5h; the multi-energy field includes ultrasound, microwave and steady magnetic field; the ultrasound frequency is 80kHz, and the power is 310W; the microwave frequency is 2.7GHz, and the power is 1250W; the magnetic field strength of the steady magnetic field is 16000Gs.

[0087] The iodine salt aqueous solution in step S3 is a potassium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.12 mol / L; the parameters of the electrophoretic deposition of iodine in step S3 are: the distance between the working electrode and the counter electrode is 22 cm, the deposition time is 35 min, the constant voltage is 75 V, the temperature is 30 ° C, and it is carried out under light-proof conditions; the specific parameters of the ion implantation method in step S4 are: ion flux 160 keV, trigger frequency 7 Hz, arc voltage 120 V, acceleration voltage 50 kV, arc current 0.8 A, suppression voltage 3.5 kV, vacuum degree 5× 10 -4 Pa.

[0088] In the povidone iodine / food-grade water-soluble chitosan dipping solution described in step S5, the mass percentage concentration of food-grade water-soluble chitosan is 6wt%, and the mass percentage concentration of povidone iodine is 1wt%; the viscosity-average molecular weight of the food-grade water-soluble chitosan is 120,000, and the degree of deacetylation is 90%; the drying temperature described in step S5 is 95°C.

[0089] A medical antibacterial coating prepared by the preparation method of the medical antibacterial coating.

[0090] Comparative Example 1, a medical antibacterial coating and a preparation method thereof, is basically the same as Example 1, except that there is no multi-energy field-assisted treatment and zinc loading step.

[0091] Comparative Example 2, a medical antibacterial coating and a preparation method thereof, is basically the same as Example 1, except that there is no surface modification and electrophoretic deposition iodine loading step.

[0092] In order to further illustrate the beneficial technical effects of the medical antibacterial coating involved in each embodiment of the present invention, relevant performance tests were carried out on the medical antibacterial coating involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the antibacterial property of the coating surface is detected by the film sticking method, referring to the national standard GB / T 31402-2015 "Plastic-Plastic Surface Antibacterial Property Test Method", and the selected bacteria are Escherichia coli (ATCC 8099) and Staphylococcus aureus (ATCC 6538).

[0093]

[0094] It can be seen from the data in Table 1 that the medical antibacterial coatings involved in the embodiments of the present invention have better antibacterial properties and antibacterial stability than the comparative products; the combined use of multi-energy field assisted treatment, zinc loading step, surface modification and electrophoretic deposition iodine loading step is beneficial to improving the above properties.

[0095] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a medical antibacterial coating, characterized in that: The steps include: Step S1, pretreatment: polish the surface of the medical titanium or titanium alloy sample to a mirror surface, then ultrasonically clean it with acetone, distilled water and anhydrous ethanol in sequence, and finally dry it with cold air to obtain a pretreated sample; Step S2, two-step anodization: prepare a fluorine-containing electrolyte, use the pretreated sample as the anode and the platinum sheet as the cathode to perform the first step of anodization in the fluorine-containing electrolyte, then use a hydrochloric acid solution for ultrasonic cleaning for 0.5-1h, blow dry with cold wind, use the sample after the first step of anodization as the anode and graphite as the cathode to perform the second step of anodization in the fluorine-containing electrolyte, wash with water and dry after the reaction, and then place the treated sample in a muffle furnace for calcination to obtain a sample with micro-nano surface modification; In the first step of anodization, a multi-energy field is used for auxiliary treatment for 10-15 minutes; in the second step of anodization, a multi-energy field is used for auxiliary treatment for 15-20 minutes; the fluorine-containing electrolyte comprises the following components in weight percentage: ammonium fluoride 0.5-2.5wt%, glycerol 20-30wt%, tris(hydroxymethyl)aminomethanesulfonic acid 1-3wt%, saccharin sodium 0.3-1wt%, hexamethylenetetramine 0.1-0.6wt%, citric acid 1-3wt%, calcium dihydrogen phosphate 0.1-0.4wt%, and the balance is deionized water; the multi-energy field comprises ultrasound, microwave and steady magnetic field; the ultrasound frequency is 40-80kHz, and the power is 90-310W; the microwave frequency is 2.0-2.7GHz, and the power is 550-1250W; the magnetic field strength of the steady magnetic field is 6000-16000Gs; Step S3, electrophoretic deposition of iodine: using an iodine salt aqueous solution as a deposition liquid, a sample with micro-nano surface modification as a working electrode, and a platinum sheet as a counter electrode to perform electrophoretic deposition of iodine to obtain an iodine-loaded sample; the iodine salt aqueous solution is a potassium iodide aqueous solution or a sodium iodide aqueous solution; the concentration of the iodine salt aqueous solution is 0.06-0.12 mol / L; the parameters of the electrophoretic deposition of iodine are: the distance between the working electrode and the counter electrode is 8-22 cm, the deposition time is 10-35 min, the constant voltage is 25-75 V, the temperature is 20-30° C., and it is performed under light-proof conditions; Step S4, loading zinc: using ion implantation method, zinc is used as target material, zinc is implanted into the iodine-loaded sample, and a sample with iodine / zinc loaded on the surface is obtained; the specific parameters of the ion implantation method are: ion flux 140-160 keV, trigger frequency 4-7 Hz, arc voltage 70-120 V, acceleration voltage 25-50 kV, arc current 0.3-0.8 A, suppression voltage 1.5-3.5 kV, vacuum degree 1×10 -4 ~5×10 -4 Pa; Step S5, surface modification: immersing the iodine / zinc loaded sample prepared in step S4 into a povidone iodine / food-grade water-soluble chitosan dipping solution for 8-25 seconds, taking it out and drying it to constant weight to obtain a medical antibacterial coating; in the povidone iodine / food-grade water-soluble chitosan dipping solution, the mass percentage concentration of food-grade water-soluble chitosan is 1-6wt%, and the mass percentage concentration of the povidone iodine is 0.3-1wt%; the viscosity-average molecular weight of the food-grade water-soluble chitosan is 100,000-120,000, and the degree of deacetylation is 90%; the drying temperature is 90-95°C.

2. The method for preparing the medical antibacterial coating according to claim 1, characterized in that: The ultrasonic cleaning has an ultrasonic frequency of 60-100 kHz and a power of 300-400 W.

3. The method for preparing the medical antibacterial coating according to claim 1, characterized in that: The parameters of the first step of anodization in step S2 are: voltage of 40-100V, distance between anode and cathode of 8-15cm, temperature of 20-30°C, time of 1-3h; the volume percentage concentration of the hydrochloric acid solution in step S2 is 4-20vol%.

4. The method for preparing the medical antibacterial coating according to claim 1, characterized in that: The parameters of the second step of anodization in step S2 are: voltage of 18-52V, distance between anode and cathode of 5-10cm, temperature of 20-30°C, and time of 3-6h; the calcination temperature in step S2 is 440-610°C, and the calcination time is 1-5h.

5. A medical antibacterial coating prepared by the preparation method of the medical antibacterial coating according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Method for preparing biomedical titanium and titanium alloy surface antibacterial coatings

    CN102758202B

  • Design and preparation method of chitosan-iodide antibacterial coating of titanium alloy implant

    CN103656748A

  • Surface modification method for implant materials of biomedical active titanium and alloy of biomedical active titanium

    CN107693843A